The case for investment in tobacco control: lessons from four countries in the Americas - Brian Hutchinson; Farisha Brispat; Lorena Viviana Calderón Pinzón; Alejandra Sarmiento; Esteban Solís; Rachel Nugent; Nathan Mann; Garrison Spencer; Carrie Ngongo; Andrew Black; Maria Carmen Audera-Lopez; Tih Armstrong Ntiabang; et al. (Pan American Health Organization, 2022)
Objective. To synthesize learnings from four national tobacco control investment cases conducted in the Americas (Colombia, Costa Rica, El Salvador, Suriname) under the World Health Organization Framework Convention on Tobacco Control (WHO FCTC) 2030 project, to describe results and how national health authorities have used the cases, and to discuss implications for the role of investment cases in advancing tobacco control. Methods. We draw on findings from four national investment cases that included 1) a cost-of-illness analysis calculating the health and economic burden of tobacco use, 2) a return-on-investment analysis of implementing key tobacco control demand reduction measures, and 3) a subsidiary analysis of one tobacco control topic of national interest (e.g., equity implications of cigarette taxation). Co-authors reported how cases have been used to advance tobacco control. Results. In Colombia, Costa Rica, El Salvador, and Suriname, tobacco use causes social and economic losses equivalent to between 1.0 to 1.8 percent of GDP. Across these countries, implementing WHO FCTC demand reduction measures would save an average of 11 400 lives per year over the next 15 years. Benefits of the measures would far outweigh the costs of implementation and enforcement. Governments are using the cases to advance tobacco control, including to improve tobacco control laws and their enforcement, strengthen tobacco taxation, prioritize tobacco control planning, coordinate a multisectoral response, and engage political leaders. Conclusions. National investment cases can help to strengthen tobacco control in countries, including by increasing public and political support for implementation of the WHO FCTC and by informing effective planning, legislation, coordination and financing.